Work-life balance in managing stress, job satisfaction and performance: the wasatiyyah concept and neuroscience perspective - Zolkefley, M K I; Che Mohd Nassir, Che Mohd Nasril; Jaffer, Usman (Universiti Sultan Azlan Shah (USAS), 2023)
The relationship between work-l!fe imbalance with occupational burnout, and poor mental health outcomes have been widely explore. This working paper aimed to determine how the concept of equilibrium (balance) and moderateness in Islam, or wasatiyyah, could shed some light on this issue. This paper discussed the aspects that needed to be emphasized based on the wasatiyyah concept in work-life balance in managing stress, job satisfaction and work performance. The equilibrium state of four elements which comprised of biological, psychological, social, and spiritual can help to manage contemporary stress-related issues. In addition, the application of wasatiyyah concept can modulate the network and hormonal organization inside our brain which subsequently affect the performance of our daily work and activities. This ethics component in Islam is integrated in the daily life of a Muslim and bring all-round benefits, from managing stress, job satisfaction to the performance at work.